The Relevance of Rizq and Islamic Work Ethic in Tafsir Al-Misbah: A Study of Qur'an Surah al-Jumu'ah (62:10) among Online Motorcycle Taxi Drivers in Medan - Rizky Febriansyah Sinaga; Agusman Damanik (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study is motivated by the importance of understanding the balance between worship and work in Islam specifically based on Surah Al-Jumu’ah, verse 10 amidst the pressures of the digital economy faced by online motorcycle taxi drivers in Medan. The research aims to analyze the relevance of the concepts of rizq (divine provision) and the Islamic work ethic, as presented in the Al-Misbah exegesis, to the drivers' mindsets and mental resilience. A descriptive qualitative method was employed, utilizing interviews, observation, and documentation involving three informants. The findings reveal that drivers perceive work as an act of worship, integrating values such as tawakkul (reliance on God), amanah (trustworthiness), and dhikr (remembrance of God) into their daily activities, despite facing pressures from algorithms and market competition. Spiritual values were shown to help maintain work ethics and mental stability. In conclusion, Surah Al-Jumu’ah, verse 10, serves as an ethical foundation that fosters a balance between economic productivity and spirituality, ensuring that work is oriented not merely toward material gain but also toward divine blessing and the greater good of life